Basic researchAntioxidative potential of black tea polyphenols in vitro and protective effects in vivo on mitochondrialredox status during experimental oral carcinogenesis - Letchoumy, P. Vidjaya; Mohan, K.V.P. Chandra; Hara, Yukihiko; Nagini, Siddavaram (Archives of Medical Science, 2007)
Introduction: To evaluate the in vitro and in vivo antioxidant properties of the black tea polyphenols Polyphenon-B and BTF-35. Material and methods: The in vitro antioxidant activity of black tea polyphenols was screened using a panel of assays including 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2’-azinobis-(3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS), hydroxyl radical anion (OH • ), superoxide anion (O 2 •– ), and nitric oxide (NO) radical scavenging assays as well as assay for reducing power. The in vivo antioxidant potential was evaluated in the 7,12-dimethylbenz[a]anthracene (DMBA)-induced hamster buccal pouch (HBP) carcinogenesis model. Hamsters were divided into 6 groups. Animals in groups 1 to 3 were painted with 0.5% DMBA three times a week for 14 weeks. While hamsters in group 1 received no further treatment, animals in groups 2 and 3 received a diet containing 0.05% Polyphenon-B and BTF-35 respectively, from four weeks before DMBA painting until the end of the experiment. Animals in groups 4 and 5 were given Polyphenon-B and BTF-35 alone respectively, and group 6 animals served as controls. All the animals were sacrificed after 18 weeks. Results: In in vitro studies, both Polyphenon-B and BTF-35 showed high radical scavenging activity and reductive potential. Dietary administration of Polyphenon-B and BTF-35 suppressed DMBA-induced HBP tumours by modulating mitochondrial lipid and protein oxidation and enhancing manganese superoxide dismutase (MnSOD), catalase (CAT), reduced glutathione (GSH) and GSH-dependent enzymes in the buccal pouch and liver. Conclusions: Our study suggests that the antioxidative properties of tea polyphenols may be responsible for chemoprevention of HBP carcinogenesis. Of the two tea polyphenols analysed, BTF-35 was more effective than Polyphenon-B both in vitro and in vivo .